The Implementation of Independent Curriculum in Sekolah Penggerak - Meilina Haris Mayekti; Dinar Faiza (Jurnal Vokasia, 2023)
This study is a descriptive qualitative method, which is describes about the situation and the data obtained during observations and questions. It becomes useful information and will be easily understood by readers. The purpose of this study was to identify and obtain information about the implementation of the independent curriculum in sekolah penggerak.. This study explains and provides about the implementation of the independent curriculum in “sekolah penggerak”. The results of this study was the the implementation of the curriculum in the “sekolah penggerak” has been carried out optimally and is ongoing, although in practice there are still many shortcomings and obstacles. The way to be success of implementing the curriculum in “sekolah penggerak” is that the headmaster and teachers must have the will to do changes. The headmaster as a leader must be able to change the mindset of the Human Resources in the school to want to do changes so that the independent curriculum can be applied.